Torsional Strength of Beams Made of Reactive Powder Concrete Containing Recycled Aggregate - salahuddin qusay (Misan Journal of Engineering Sciences)
This study investigates the torsional strength of beams made of a reactive powder concrete mix containing fine recycled aggregate. It also studies the mechanical properties of reactive powder concrete (RPC) in its fresh and hard state and the impacts of replacing it with recycled aggregate in different grading sizes. Seven RPC beams were examined and divided into two groups: the first group (control 0%, 20%, 40%, and 60%) of replacement with natural fine aggregate (600µm) and the second group at constant replacement 40% with different grading maximum sizes (1.18 mm, 2.36 mm, and 4.75 mm). The results indicate that reactive powder concrete at 40% replacement and particle size 2.36 mm of recycled aggregate gives the highest result regarding torsion behavior strength.